PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING TERINTEGRASI TPACK UNTUK PENINGKATAN HASIL BELAJAR IPAS SD - Rini Esti Rahayu; Daimul Hasanah; Heri Maria Zulfiati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The rapid development of technology from year to year makes an educator must be able to improve his abilities in the field of technology in the realm of education that has been worked on. Therefore, an educator must be able to combine the learning model that will be implemented with current technological developments so that student learning outcomes can improve. The subjects of this study were fifth grade students of SDN I Wonokerso in the 2023/2024 school year as many as 21 students where there were 9 female students and 12 male students. The purpose of this study was to determine the improvement of learning outcomes of grade V students by using the PJBL learning model integrated with TPACK. This is in line with research conducted by Tiok Setiawan that the PJBL learning model integrated with TPACK makes students active and in the learning process and learning outcomes increase. The research method used is descriptive qualitative. Where data collection uses interviews and observations. This research shows that 91% of students have improved their learning outcomes. So it can be concluded that by using the PJBL learning model integrated with TPACK, the learning outcomes of grade V students in IPAS subjects increase, besides that students are also more active and enthusiastic in participating in the learning process.